Safety, efficacy and cost effectiveness of Palivizumab in high risk infants. (24th May 2012) - Abusamra, R; Schofield, M; Minasian, CC
Abstract : Aim: A four-year retrospective review of the safety and efficacy of Palivizimab in the prophylaxsis of respiratory syncitial virus (RSV) in high risk infants Background: RSV is the leading viral pathogen responsiible for hospitalisation with lower respiratory tract infection in high risk infants. It accounts for 20, 000 admissions /year in the United Kingdom. 90% of infants are infected by 2 years of age. A previous randomised controlled study reported a 55% reduction in RSV-related hospitalisations with passive immunoprophylaxis with the human monoclonal antibody Paluvizimab.1 It was also found to be safe. Methods: We conducted a retrospective study of all high risk infants admitted to a paediatric department of a teaching hospital between 2006 and 2010. Inclusion criteria included children under 2 years with chronic lung disease or on home oxygen, those with congenital immunodeficiency and infants under 6 months with congenital heart disease. Children received five intramuscular injections of Palivizimab (15 mg/kg) every 30 days (total of 5 doses) during the RSV season (October-November). Data was collected from the clinical notes and electronic patient record on demographics, underlying diagnosis, side-effects and confirmed RSV infection A cost-analysis was also performed. Results: Records on 61 patients were examined. 5 children did not meet the study criteria. A total of 41 patients completed the course of immunoprophylaxis. Data on RSV infection was available for 52/61 patients. Of these children, none of those who received a complete course of prophylaxis developed RSV infection. Reported side-effects were all mild with the exception of one child with a seizure disorder who had an increase in fit frequency. Having dedicated clinics for administering Palivizimab allowed sharing of opened vials between patients and more effective utilisation of clinic staff and resources. A total of £15, 000 was saved from the total budget of £50, 000 by adopting this strategy Conclusions: This is first study to examine the safety and efficacy of Palivizimab since 1998. Our results confirm that RSV prophylaxis is safe and effective in preventing RSV infection in high risk infants. Additionally, we have used simple strategies to further reduce drug costs and improve cost effectiveness